Law Enforcement of Criminal Acts of Smuggling Illegal Export-Import Goods in Indonesian Waters - Rahmawati, Iis (AHKAM, 2022)
The purpose of this study is to find out and analyze law enforcement in the field of customs, against the smuggling of illegal export-import goods in the territory of Indonesia. The research method used is a qualitative method using a legal approach and a conceptual approach. Data sources are primary data and secondary data. Based on the research findings, cases of smuggling illegal export-import goods are increasing every year, with various types of illegal goods. This is because it is influenced by several factors, one of which is the geographical factor of Indonesia which has many islands that are opportunities for smuggling illegal goods, in addition to geographical factors are also influenced by natural resources, industrial conditions, overproduction, and transportation. Smuggling of export-import goods is a criminal offense that has been regulated in various Indonesian laws and regulations. As for law enforcement efforts carried out, namely by taking preventive measures by monitoring and checking people or goods suspected of committing customs crimes, in addition to preventive efforts, repressive efforts are also carried out, namely law enforcement in the form of investigations, arrests, prosecutions, to prosecutions by imposing criminal penalties by the court.